Innovation in Services - Theoretical Approach - Wyszkowska-Kuna, Joanna (Comparative Economic Research. Central and Eastern Europe, 2012)
The aim of this article is to present the evolution of theoretical studies on service innovation. The author also attempts to put these different approaches to service innovation into order and to indicate the possible forms of service innovation that emerge from these researches. In further part of the article the issue of the availability of statistical data and its relevance to the possible forms of service innovation, as well as some changes that has been implemented recently in order to improve this relevance, are discussed.